KALIANYAR VERTICAL KAMPONG WITH BEHAVIOR ARCHITECTURE IN JAKARTA - El Yanno Suminar; Marsudi Marsudi; Kusumaningdyah Nurul Handayani (Universitas Sebelas Maret Surakarta, 2016)
Vertical Kampung Kalianyar design was motivated by data and facts related to the city of Jakarta and some issue as a city that has problems of population density. Jakarta is not the only city that has a population density problems, almost all cities in Indonesia have similar problems against the background of the dominance of urbanization which resulted in the high number of population in urban areas. Most of the problems of population density pose problems of urban spatial structure damage caused by the emergence of slum areas or slums in urban areas some point including the city of Jakarta. Kampung is one of the many forms of settlement which is located in the slum area and pay attention to the spatial structure of the city badly. Kampung Kalianyar is one of the densely populated area in the city of Jakarta which has poor spatial structure. On the other hand, as the settlements, Kampung Kalianyar has its own values and character are formed from several things, one of which is a sense of togetherness with the similarity of the social level. Problem of density in Jakarta has tried to be solved by Jakarta Provincial Government with rumah susun program to accommodate flats dense settlements, but it is considered less than optimal because of the character of residents of rumah susun is not contained in it. This is the destination of Kampung Vertical Kalianyar with the basis of behavior architecture as design concept to accommodate the character of Kampung Kalianyar with methods of observation and mapping that is performed directly in Kampung Kalianyar to be applied into a new form named Kampung Vertical Kalianyar. Results from analysis through observation and mapping will be transformed into a new form as knwon as Kampung Vertical Kalianyar which is able to accommodate all the character and behavior of Kampung Kalianyar like life on the road space which has been the character and social value of Kampung Kalianyar and the units of home base enterprises in every floor level.